Effects of Chemogenetic Inhibition of D1 or D2 Receptor-Containing Neurons of the Substantia Nigra and Striatum in Mice With Tourette Syndrome - Lin, Lixue; Lan, Yuye; Zhu, He; Yu, Lingling; Wu, Shuang; Wan, Wangyixuan; Shu, Yang; Xiang, Hongchun; Hou, Tengfei; Zhang, Hong; Ma, Yan; Su, Wen; et al. (Frontiers in Molecular Neuroscience, 2021)
As Tourette syndrome (TS) is a common neurobehavioral disorder, the primary symptoms of which include behavioral stereotypies. Dysfunction of the substantia nigra - striatum network could be the main pathogenesis of TS, which is closely associated with dopamine and its receptors. TS is often resistant to conventional treatments. Therefore, it is necessary to investigate the neurobiological mechanisms underlying its pathogenesis. In this study, we investigated whether chemogenetic activation or inhibition of dopamine D1 receptor (D1R) or D2 receptor (D2R)-containing neurons in the substantia nigra pars compacta (SNpc) or dorsal striatum (dSTR) affected the stereotyped behavior and motor functions of TS mice. Intraperitoneal injection of 3,3’- iminodipropionitrile (IDPN) was used to induce TS in mice. Stereotyped behavior test and open field, rotarod, and grip strength tests were performed to evaluate stereotyped behavior and motor functions, respectively. Immunofluorescence labeling was used to detect the co-labeling of virus fluorescence and D1R or D2R. We found that chemogenetic inhibition of D1R or D2R-containing neurons in the SNpc and dSTR alleviated behavioral stereotypies and motor functions in TS mice. Chemogenetic activation of D1R-containing neurons in the dSTR aggravated behavioral stereotypies and motor functions in vehicle-treated mice, but neither were aggravated in TS mice. In conclusion, chemogenetic inhibition of D1R or D2R-containing neurons in the SNpc and dSTR alleviated behavioral stereotypies of TS, providing a new treatment target for TS. Moreover, the activation of D1R-containing neurons in the dSTR may contribute to the pathogenesis of TS, which can be chosen as a more precise target for treatment.